Mental Health in the Perspective of Hadith: Utsman Najati’s Concept and its Contribution to Islamic Education - Fauzy, Daffa Nur; Setiawan, Farid; Thufail Amrullah, Ammar (Universitas Ahmad Dahlan, 2025)
This study aims to analyze the concept of mental health in the thought of M. Utsman Najati and its contribution to the Islamic education paradigm. The research employs a qualitative approach, utilizing thematic analysis and hadith contextualization, to interpret the integration between revelation and psychology. The findings indicate that Najati’s key contribution is challenging the reductionist tendency of Western psychology by integrating spiritual, psychological, social, and biological dimensions into a unified, prophetic paradigm as the basis for achieving inner balance (at-tawāzun an-nafsī). He introduces a conceptual model for Islamic education that aims to develop the insān kāmil (complete human being), characterized by emotional stability, mental health, and spiritual resilience. The study’s novelty lies in using hadith as an epistemological source for Islamic mental health theory and applying a prophetic-psychological approach to character education. However, this study does not empirically test Najati’s concept within educational institutions. Therefore, future research is recommended to develop pedagogical models and mental health assessment instruments grounded in Islamic spirituality, to enhance the effectiveness of Islamic education in nurturing a resilient generation rooted in tawḥīd values.